# |
ODE |
Mathematica |
Maple |
\[
{}x {y^{\prime }}^{2}+\left (1-x \right ) y y^{\prime }-y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}+\left (1-x^{2} y\right ) y^{\prime }-x y = 0
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right ) {y^{\prime }}^{2} = y
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right ) {y^{\prime }}^{2}-\left (x +y\right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}\left (a -x \right ) {y^{\prime }}^{2}+y y^{\prime }-b = 0
\] |
✓ |
✓ |
|
\[
{}2 x {y^{\prime }}^{2}+\left (2 x -y\right ) y^{\prime }+1-y = 0
\] |
✓ |
✓ |
|
\[
{}3 x {y^{\prime }}^{2}-6 y y^{\prime }+x +2 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (1+3 x \right ) {y^{\prime }}^{2}-3 \left (y+2\right ) y^{\prime }+9 = 0
\] |
✓ |
✓ |
|
\[
{}\left (3 x +5\right ) {y^{\prime }}^{2}-\left (3+3 y\right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}4 x {y^{\prime }}^{2} = \left (a -3 x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}4 x {y^{\prime }}^{2}+2 x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}4 x {y^{\prime }}^{2}-3 y y^{\prime }+3 = 0
\] |
✓ |
✓ |
|
\[
{}4 x {y^{\prime }}^{2}+4 y y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}4 x {y^{\prime }}^{2}+4 y y^{\prime }-y^{4} = 0
\] |
✓ |
✓ |
|
\[
{}4 \left (2-x \right ) {y^{\prime }}^{2}+1 = 0
\] |
✓ |
✓ |
|
\[
{}16 x {y^{\prime }}^{2}+8 y y^{\prime }+y^{6} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2} = a^{2}
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2} = y^{2}
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2}+x^{2}-y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2} = \left (x -y\right )^{2}
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2}+y^{2}-y^{4} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2}-x y^{\prime }+y \left (1-y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2}+2 a x y^{\prime }+a^{2}+x^{2}-2 a y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2}-2 x y y^{\prime }-x +y \left (1+y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2}-2 x y y^{\prime }-x^{4}+\left (-x^{2}+1\right ) y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2}-\left (1+2 x y\right ) y^{\prime }+1+y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2}-\left (a +2 x y\right ) y^{\prime }+y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2}-x \left (x -2 y\right ) y^{\prime }+y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2}+2 x \left (y+2 x \right ) y^{\prime }-4 a +y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2}+x \left (x^{3}-2 y\right ) y^{\prime }-\left (2 x^{3}-y\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2}+3 x y y^{\prime }+2 y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2}-3 x y y^{\prime }+x^{3}+2 y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2}+4 x y y^{\prime }-5 y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2}-4 x \left (y+2\right ) y^{\prime }+4 y \left (y+2\right ) = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2}-5 x y y^{\prime }+6 y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2}+x \left (x^{2}+x y-2 y\right ) y^{\prime }+\left (1-x \right ) \left (x^{2}-y\right ) y = 0
\] |
✗ |
✗ |
|
\[
{}x^{2} {y^{\prime }}^{2}+\left (y+2 x \right ) y y^{\prime }+y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2}+\left (2 x -y\right ) y y^{\prime }+y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2}+\left (a +b \,x^{2} y^{3}\right ) y^{\prime }+a b y^{3} = 0
\] |
✓ |
✓ |
|
\[
{}\left (-x^{2}+1\right ) {y^{\prime }}^{2} = 1-y^{2}
\] |
✓ |
✓ |
|
\[
{}\left (-x^{2}+1\right ) {y^{\prime }}^{2}+2 x y y^{\prime }+4 x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (a^{2}+x^{2}\right ) {y^{\prime }}^{2} = b^{2}
\] |
✓ |
✓ |
|
\[
{}\left (a^{2}-x^{2}\right ) {y^{\prime }}^{2}+b^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (a^{2}-x^{2}\right ) {y^{\prime }}^{2} = b^{2}
\] |
✓ |
✓ |
|
\[
{}\left (a^{2}-x^{2}\right ) {y^{\prime }}^{2} = x^{2}
\] |
✓ |
✓ |
|
\[
{}\left (a^{2}-x^{2}\right ) {y^{\prime }}^{2}+2 x y y^{\prime }+x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (a^{2}-x^{2}\right ) {y^{\prime }}^{2}-2 x y y^{\prime }-y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (a^{2}+x^{2}\right ) {y^{\prime }}^{2}-2 x y y^{\prime }+b +y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{2} {y^{\prime }}^{2}-4 x y y^{\prime } = 8 x^{3}-y^{2}
\] |
✓ |
✓ |
|
\[
{}a \,x^{2} {y^{\prime }}^{2}-2 a x y y^{\prime }+a \left (1-a \right ) x^{2}+y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (-a^{2}+1\right ) x^{2} {y^{\prime }}^{2}-2 x y y^{\prime }-a^{2} x^{2}+y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} {y^{\prime }}^{2} = a
\] |
✓ |
✓ |
|
\[
{}x^{3} {y^{\prime }}^{2}+x y^{\prime }-y = 0
\] |
✓ |
✗ |
|
\[
{}x^{3} {y^{\prime }}^{2}+x^{2} y y^{\prime }+a = 0
\] |
✓ |
✓ |
|
\[
{}x \left (-x^{2}+1\right ) {y^{\prime }}^{2}-2 \left (-x^{2}+1\right ) y y^{\prime }+x \left (1-y^{2}\right ) = 0
\] |
✓ |
✓ |
|
\[
{}4 x \left (a -x \right ) \left (-x +b \right ) {y^{\prime }}^{2} = \left (a b -2 x \left (a +b \right )+2 x^{2}\right )^{2}
\] |
✓ |
✓ |
|
\[
{}x^{4} {y^{\prime }}^{2}-x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}x^{4} {y^{\prime }}^{2}+2 x^{3} y y^{\prime }-4 = 0
\] |
✓ |
✓ |
|
\[
{}x^{4} {y^{\prime }}^{2}+y^{2} y^{\prime } x -y^{3} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} \left (a^{2}-x^{2}\right ) {y^{\prime }}^{2}+1 = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{4} {y^{\prime }}^{2}-x y-y = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{5} {y^{\prime }}^{2}+12 x^{4} y y^{\prime }+9 = 0
\] |
✓ |
✓ |
|
\[
{}x^{6} {y^{\prime }}^{2}-2 x y^{\prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{8} {y^{\prime }}^{2}+3 x y^{\prime }+9 y = 0
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2} = a
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2} = x \,a^{2}
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2} = {\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2}+2 a x y^{\prime }-a y = 0
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2}-4 a^{2} x y^{\prime }+a^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2}+a x y^{\prime }+b y = 0
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2}-\left (-2 b x +a \right ) y^{\prime }-b y = 0
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2}+x^{3} y^{\prime }-x^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2}+\left (x -y\right ) y^{\prime }-x = 0
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2}-\left (x +y\right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2}-\left (x y+1\right ) y^{\prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2}+\left (x -y^{2}\right ) y^{\prime }-x y = 0
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2}+y = a
\] |
✓ |
✓ |
|
\[
{}\left (x +y\right ) {y^{\prime }}^{2}+2 x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}\left (2 x -y\right ) {y^{\prime }}^{2}-2 \left (1-x \right ) y^{\prime }+2-y = 0
\] |
✓ |
✓ |
|
\[
{}2 y {y^{\prime }}^{2}+\left (5-4 x \right ) y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}9 y {y^{\prime }}^{2}+4 x^{3} y^{\prime }-4 x^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}\left (1-a y\right ) {y^{\prime }}^{2} = a y
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-a y\right ) {y^{\prime }}^{2}-2 x y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y {y^{\prime }}^{2}+\left (x +y\right ) y^{\prime }+1 = 0
\] |
✓ |
✓ |
|
\[
{}x y {y^{\prime }}^{2}+\left (x^{2}+y^{2}\right ) y^{\prime }+x y = 0
\] |
✓ |
✓ |
|
\[
{}x y {y^{\prime }}^{2}+\left (x^{2}-y^{2}\right ) y^{\prime }-x y = 0
\] |
✓ |
✓ |
|
\[
{}x y {y^{\prime }}^{2}-\left (x^{2}-y^{2}\right ) y^{\prime }-x y = 0
\] |
✓ |
✓ |
|
\[
{}x y {y^{\prime }}^{2}+\left (a +x^{2}-y^{2}\right ) y^{\prime }-x y = 0
\] |
✓ |
✗ |
|
\[
{}x y {y^{\prime }}^{2}-\left (a -b \,x^{2}+y^{2}\right ) y^{\prime }-b x y = 0
\] |
✓ |
✗ |
|
\[
{}x y {y^{\prime }}^{2}+\left (3 x^{2}-2 y^{2}\right ) y^{\prime }-6 x y = 0
\] |
✓ |
✓ |
|
\[
{}x \left (x -2 y\right ) {y^{\prime }}^{2}-2 x y y^{\prime }-2 x y+y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x \left (x -2 y\right ) {y^{\prime }}^{2}+6 x y y^{\prime }-2 x y+y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{2} {y^{\prime }}^{2} = a^{2}
\] |
✓ |
✓ |
|
\[
{}y^{2} {y^{\prime }}^{2}-a^{2}+y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{2} {y^{\prime }}^{2}-3 x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{2} {y^{\prime }}^{2}-6 x^{3} y^{\prime }+4 x^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}y^{2} {y^{\prime }}^{2}-4 a y y^{\prime }+4 a^{2}-4 a x +y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{2} {y^{\prime }}^{2}-\left (1+x \right ) y y^{\prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}y^{2} {y^{\prime }}^{2}+2 x y y^{\prime }+x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{2} {y^{\prime }}^{2}+2 x y y^{\prime }+a -y^{2} = 0
\] |
✓ |
✓ |
|